Pengaruh Masa Perikatan Audit, Rotasi Kap, Ukuran Perusahaan Dan Ukuran Kap Terhadap Kualitas Audit ( Studi Empiris Pada Perusahaan Manufaktur Kimiayang Terdaftar di Bursa Efek Indonesia (BEI) periode 2011-2014) - Dwi Hastutik, Retno, Dra. Nursiam, M.H., Ak., CA (2016)
To achieve the quality of information is expected, needed a quality inspection. In this study, future audit quality associated with the audit engagement, the rotation size public accounting firm as well as the size of the public accounting firm because these three things are considered may affect the quality of audit. The sample in this research is manufacturing chemistry companies listed in Indonesia Stock Exchange (BEI) and still active from year 2011 to 2014 consisting of 10 companies for each year that the sample in this study is 40. Data analysis techniques used in this study using multiple regression analysis logistics. Research showing the audit engagement does not affect the quality of the audit indicated the significance value 0.905> 0.05. KAP rotation does not affect the quality of the audit indicated the significance value of 0.988> 0.05. Company size does not affect the quality of the audit indicated the significance value of 0.324> 0.05. Firm size does not affect the quality of the audit indicated with a significance value of 0.906> 0.05. Firm size does not affect the quality of the audit indicated with a significance value of 0.906> 0.05. Keywords: audit tenure, rotation of the office of public accountant, company size, size of public accounting firms. audit quality.